Circular economy-based reverse logistics: dynamic interplay between sustainable resource commitment and financial performance - Fernando, Yudi; Muhammad Shabir, Shaharudin; Ahmed Zainul, Abideen (Emerald Publisher, 2022)
Purpose: The study aims to propose a circular economy-based reverse logistics (CERL) that emphasises the mediation effect of reverse logistics (RL) on sustainable resource commitment and financial performance. Design/methodology/approach:The structural equation modelling (SEM) approach has been applied to analyse the data acquired through the survey method that included 113 vendors of automotive supplies of the 1st and 2nd levels. Findings:The results confirm that CERL acts as an essential intervening entity between resources and financial performance. The findings of the study have provided research and development (R&D) opportunities for the industries to find alternative revenue streams and generate profit from resource investment whilst upholding environmental standards through reverse logistic practices. Practical implications: Reverse logistic practices are the key components of a circular business model and a sustainable supply chain. The manufacturing companies need to explore critical enablers that can contribute to business productivity and financial growth. Originality/value: The study has validated a CERL model that portrays the circular economy's resilient relationship with RL practices.